DINAMIKA HUBUNGAN ISLAM DAN NEGARA: PEMIKIRAN POLITIK ISLAM DI INDONESIA - Imam Hafizar Rifki (CV. Denasya Smart Publisher, 2025)
The relationship between Islam and the state in Indonesia is a crucial issue in the history of Islamic political thought. As a country with a Muslim-majority population, Indonesia faces the challenge of integrating Islamic values with a modern governance system based on Pancasila. This article examines the dynamics of the relationship between Islam and the state in Indonesia, focusing on the thoughts of Islamic scholars, the role of the Jakarta Charter, and the implementation of Islamic values in a pluralistic national context. This study employs a literature review method, analyzing books, articles, and previous research. The findings reveal that the relationship between Islam and the state in Indonesia is dynamic, where Islam can contribute as a source of ethical values without being formalized. In conclusion, this dynamic reflects the efforts of Muslims to balance religious identity with national needs, thereby strengthening national unity and contributing positively to the nation's development.